1989
DOI: 10.1016/0741-5214(89)90057-8
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic severe carotid stenosis

Abstract: The management of asymptomatic carotid stenosis remains controversial. From December 1983 to December 1987, 188 symptom-free patients were found to have severe (>75%) stenosis by duplex imaging (performed as screening examination). Patients with nonhemispheric symptoms or contralateral symptomatic lesions (within 7 years) were excluded from the study. Follow-up data were available for 141 patients (range 3 to 36 months; mean 21 months). Sixty-two patients received nonoperative therapy. The remaining 79 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…After screening of 5915 unique reports and assessing the full texts of 231 for eligibility, we included 73 studies reporting 28 625 patients with ≥50% ACAS (Figure 1; Table S2). 8–10,16–85…”
Section: Resultsmentioning
confidence: 99%
“…After screening of 5915 unique reports and assessing the full texts of 231 for eligibility, we included 73 studies reporting 28 625 patients with ≥50% ACAS (Figure 1; Table S2). 8–10,16–85…”
Section: Resultsmentioning
confidence: 99%
“…Prior to the published report of ACAS in 1995, a number of smaller uncontrolled studies had suggested that patients with asymptomatic severe stenosis were at risk for future ischemic cerebrovascular events and might benefit from prophylactic CEA. 12,[14][15][16][17][18][19] Norris et al 20 found that with a stenosis greater than 75%, the combined TIA and stroke rate was 10.5% per year, with 75% of the events ipsilateral to the stenotic artery. Additionally, the North American Symptomatic Carotid Endarterectomy Trial (NASCET) 21 demonstrated a higher risk of stroke in the medically treated patients as the degree of stenosis increased.…”
Section: Risk Of "Severe" Stenosis In the Asymptomatic Patientmentioning
confidence: 99%
“…Schwartz et al 21 also found that the risk of postoperative stroke increased with increasing severity of disease ; 3·8 per cent of patients with a unilateral stenosis greater than 50 per cent suffered a hemispheric stroke, compared with 8·3 per cent of those with bilateral internal carotid artery stenosis of 80-99 per cent. The presence of an asymptomatic internal carotid artery stenosis of 50 per cent or greater is associated with a mean annual ipsilateral stroke rate of only 2·8 (range 0·9-4·7) per cent [22][23][24][25][26][27] . For patients with an asymptomatic stenosis of 75 per cent or more, the mean annual risk of stroke is 3·6 (range 1·8-10·1) per cent [28][29][30][31][32][33][34] , with only 75 per cent of strokes being ipsilateral to the stenotic artery. Three prospective randomized trials [35][36][37] designed to show the efficacy of prophylactic carotid endarterectomy in the treatment of patients with asymptomatic stenosis have failed to demonstrate that stroke or stroke-free survival is influenced by endarterectomy for asymptomatic carotid stenosis.…”
Section: Risks Of Neurological Events In Patients Undergoing Coronarymentioning
confidence: 99%